ASME/JSME 2011 8th Thermal Engineering Joint Conference 2011
DOI: 10.1115/ajtec2011-44646
|View full text |Cite
|
Sign up to set email alerts
|

Development and Experimental Validation of a Micro/Nano Thermal Ground Plane

Abstract: Heat pipes are commonly used in electronics cooling applications to spread heat from a concentrated heat source to a larger heat sink. Heat pipes work on the principles of two-phase heat transfer by evaporation and condensation of a working fluid. The amount of heat that can be transported is limited by the capillary and hydrostatic forces in the wicking structure of the device. Thermal ground planes are two-dimensional high conductivity heat pipes that can serve as thermal ground to which heat can be rejected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…A 30 mm × 30 mm × 3 mm vapor chamber thermal ground plane (Figure 29b) was recently designed, fabricated, and tested in an effort led by researchers at GE Global Research [175,176]. Device performance is extremely sensitive to small variations in the amount of initial fluid charge at this form factor; over-filling floods the condenser and under-filling may lead to premature dryout.…”
Section: Micro/nanostructured Thermal Ground Plane (Tgp)mentioning
confidence: 99%
See 3 more Smart Citations
“…A 30 mm × 30 mm × 3 mm vapor chamber thermal ground plane (Figure 29b) was recently designed, fabricated, and tested in an effort led by researchers at GE Global Research [175,176]. Device performance is extremely sensitive to small variations in the amount of initial fluid charge at this form factor; over-filling floods the condenser and under-filling may lead to premature dryout.…”
Section: Micro/nanostructured Thermal Ground Plane (Tgp)mentioning
confidence: 99%
“…In order to ensure dissipation of the desired heat load against an exerted body force 10 times normal gravity, it was found that the properties of a sintered powder wick with 75 μm particle diameters [136,140] would avoid the capillary limitation [176]. The effective thermal conductivity of 3 prototype vapor chambers was measured as a function of the gravitational body force by mounting on a centrifuge spin table.…”
Section: Micro/nanostructured Thermal Ground Plane (Tgp)mentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 15 samples were tested three times to provide sufficient statistical data. Variation in measured effective thermal conductivity is attributed to local porosity variation within the sample [23]. As shown in Figure 5, the laser flash method gives an effective thermal conductivity of about 170 W/m.K for the sintered copper wick samples when the porosity about 0.5 and this is gives 4% error -related to the uncertainty of the wick porosity-when comparing with k wick =163.2 W/m.K from Maxwell's equation.…”
Section: Theortical Modelmentioning
confidence: 96%